Management Strategies for Guidance and Counseling Services in Schools to Support Student Achievement - Marpren Karunia; Firman; Neviyarni S; Muhammad Asyraf Che Amat (Manajia: Journal of Education and Management, 2025)
Student achievement is one component of the success of the educational process. BK services have an important role in helping students overcome various obstacles that can interfere with their academic and social achievements. However, this role will not be achieved without a planned and organized management. Using the literature study method, this research analyzes various relevant sources on the management of counseling in schools, including the functions of counseling which include understanding, prevention, development, and problem solving. The results show that effective counseling management involves careful planning, proper organization, implementation in accordance with students' needs, and continuous evaluation. The involvement of various parties in the school, such as teachers, parents, and administration, is very important to create a synergy that supports the implementation of effective counseling services. In addition, the utilization of technology and supporting facilities is also an important factor in increasing the effectiveness of counseling services. This study provides practical recommendations for schools in managing counseling services to improve student achievement, especially in the midst of increasingly complex educational challenges in the modern era.